Odniesienie etyki środowiskowej do obszarów przyrodniczo cennych - Zielińska, Anetta (Environmental ethics concern towards valuable nature areas., 2008)
Environmental ethics stemmed from the concern of nature condition. As a part of ecophilosophy, environmental ethics deals with moral problems concerning the relations among a human being, groups of people, whole societies and the natural world of a man. It helps to stimulate expected attitudes and models of life which are suitable for the nature. It is important to create such a philosophy for nature protected areas which will consider the needs of people as well as the nature.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 114-123